Penerapan Kode Etik dan Asas-Asas Umum Pemerintahan yang Baik dalam Proses Penegakan Disiplin Anggota Kepolisian - Ade Santi Belianti; Suwari Akhmaddhian (Uniku Law Review, 2025)
This research is motivated by the issue of the inconsistency between the implementation of the police code of ethics and the General Principles of Good Governance (AUPB) in the process of enforcing discipline among Indonesian National Police (Polri) members. The purpose of this research is to analyze the relationship between these two norms and to assess the conformity of police officials' actions with the AUPB principles in imposing sanctions. The method used is normative legal analysis with a case study approach based on Medan Administrative Court Decision Number 20/G/2025/PTUN.MDN. The results show that although the regulation of the Polri code of ethics is normatively aligned with the AUPB, its implementation in the case studied does not meet the principles of legal certainty, accuracy, openness, and proportionality because the ethics examination process was not carried out procedurally. It is concluded that the effectiveness of code of ethics enforcement is determined not only by the firmness of sanctions but also by the consistency of the AUPB application as a guarantee of legality and fairness in fostering discipline among Indonesian National Police (Polri) members.